2020
DOI: 10.1002/ffj.3569
|View full text |Cite
|
Sign up to set email alerts
|

Variations in aroma and specific flavor in strawberry under different colored light‐quality selective plastic film

Abstract: Strawberry aroma is beneficial to the quality of the fruits and derived foods, as well as consumer health. Light quality affects strawberry aroma emission, which can be conveniently supplied by colored light‐quality selective plastic films. To produce high‐aroma strawberry by using optical colored light‐quality selective plastic film, the aroma emission and key gene expression were investigated under transparent (T), red (R), yellow (Y), green (G), blue (B), and purple (P) films. Moreover, the content of sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition to anthocyanins and soluble sugars, the results of this study also show that different light qualities variously influence fruit acid, aroma, and other quality traits. In strawberry, red light and blue light can promote the synthesis of terpenes and aromatic alcohol substances in the fruit, while blue light can reduce the acid content in the fruit ( 41 , 42 ). The results of this study confirmed this, with blue light and red light having different effects on the flavor composition of grape berries after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to anthocyanins and soluble sugars, the results of this study also show that different light qualities variously influence fruit acid, aroma, and other quality traits. In strawberry, red light and blue light can promote the synthesis of terpenes and aromatic alcohol substances in the fruit, while blue light can reduce the acid content in the fruit ( 41 , 42 ). The results of this study confirmed this, with blue light and red light having different effects on the flavor composition of grape berries after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, light quality treatments significantly affected the 2AP content in mature grain (Table 1). Previous studies have reported that there may be a 'light quality' effect on the fragrance accumulated in other plants such as strawberry and coriander leaves [33,34]. A previous study has shown that low light-induced 2AP accumulation in fragrant rice [19,20].…”
Section: Discussionmentioning
confidence: 95%
“…Flavonoids are a group of natural polyphenol substances that are abundant in vegetables and fruits and are responsible for their color, fragrance, and flavor characteristics [ 58 ]. As secondary plant metabolites, flavonoids play essential roles in many biological processes and responses to environmental factors in plants [ 59 , 60 ]. Numerous studies have revealed that flavonoid biosynthesis is not only regulated by internal genetic factors but also affected by external factors such as light, temperature, and nutritional levels [ 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As secondary plant metabolites, flavonoids play essential roles in many biological processes and responses to environmental factors in plants [ 59 , 60 ]. Numerous studies have revealed that flavonoid biosynthesis is not only regulated by internal genetic factors but also affected by external factors such as light, temperature, and nutritional levels [ 59 , 61 ]. Among them, light is one of the most important environmental factors affecting flavonoid biosynthesis in plants, which promotes fruit ripening and coloration [ 62 ].…”
Section: Discussionmentioning
confidence: 99%